1968
DOI: 10.1190/1.1439970
|View full text |Cite
|
Sign up to set email alerts
|

Geologic Implications of Aeromagnetic Data for the Eastern Continental Margin of the United States

Abstract: An aeromagnetic survey extending from the Gulf of Maine to the tip of Florida was conducted by the U. S. Naval Oceanographic Office between 1964 and 1966. Flight traverses were flown in a northwesterly direction at right angles to the geologic grain. The flight lines were approximately 800 km long and had an 8-km separation. The survey traversed part of the New England, Piedmont, and Coastal Plain provinces and extended some 320 km beyond the continental shelf into the Atlantic Ocean. Despite the wide flight-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(32 citation statements)
references
References 36 publications
2
29
0
1
Order By: Relevance
“…But the magnetic profile across it is far from flat and shows very definite traceable linear anomalies ( Figure 5), e.g., the E anomaly of Rabinowitz (1974), the Blake Spur (BS) anomaly of Taylor et al (1968), and the a anomaly of Drake et al (1963). They are quite consistent in the western Atlantic south of the Kelvin Seamounts.…”
Section: °Wsupporting
confidence: 48%
“…But the magnetic profile across it is far from flat and shows very definite traceable linear anomalies ( Figure 5), e.g., the E anomaly of Rabinowitz (1974), the Blake Spur (BS) anomaly of Taylor et al (1968), and the a anomaly of Drake et al (1963). They are quite consistent in the western Atlantic south of the Kelvin Seamounts.…”
Section: °Wsupporting
confidence: 48%
“…The structural framework of the target rocks (rocks impacted by the bolide) has been established by numerous regional seismic, gravity, and magnetic surveys ( Fig. 2; Ewing et al, 1937;Woollard et al, 1957;LeVan and Pharr, 1963;Taylor et al, 1968;Sabet, 1973;Johnson, 1977;Hawarth et al, 1980;Lyons et al, 1982;Dysart et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Pitman et al (1968) suggested that the magnetic properties of rocks of the Cretaceous quiet zone may have changed owing to diagenetic processes, a scenario that can easily be extended to include the Jurassic Quiet Zone. Indeed, the process of hydrothermal alteration of source basalts has been implied by several authors as a possible cause for the Jurassic Quiet Zone (Vogt et al, 1971;Taylor et al, 1968). Houtz and Ewing (1976) recorded a thickening of low velocity layer 2A crustal rocks associated with the Jurassic Quiet Zone and presumed there might be some connection to the change in magnetic properties therein.…”
Section: The Jurassic Quiet Zonementioning
confidence: 99%